Ferroelectrics, multiferroics and artifacts: Lozenge-shaped hysteresis and things that go bump in the night. Issue 5 (June 2018) - Scott, J.F.; Gardner, Jonathan
Graphical abstract: Abstract: This review summarizes dielectric studies and related experiments on ferroelectrics and multiferroics about which there has been considerable controversy in the literature, sometimes at unusually impolite and unprofessional levels. In addition it focuses attention on a new anomalous phenomenon – that of ferroelectric hysteresis loops P(E) that are parallelograms with straight sides. In some cases materials have been considered to be multiferroic when the data can be interpreted more simply via other well-known mechanisms. In some cases the systems truly are multiferroic, despite X-ray crystallographic data implying that this is not possible; some properties arise only from the domain walls. And in some cases authors get different results from previous work, simply because they used bulk ceramics instead of very thin films, or epitaxial films instead of randomly oriented ceramics; it is of course preferable if groups exchange specimens before they claim the work of others is simply wrong. Emphasis is on newly discovered lozenge-shaped hysteresis loops, whose parallelepiped geometries are found in four unrelated materials. This review has intentionally not discussed ferroelectric artifacts that appear in atomic force microscopy, since that is actually more extensive in variety and well reviewed this year by Kalinin's group[1] .